"Apostle of Ethnology": Agnes C. L. Donohugh's Missiological Anthropology Between the World Wars. (April 2016) - Hartley, Benjamin L.
Agnes C. L. Donohugh (1876–1966) taught at Hartford Theological Seminary's Kennedy School of Missions between 1918 and 1944, the leading graduate program in mission studies in North America prior to World War II. The first missionary student of Franz Boas at Columbia University, Donohugh influenced the shape of graduate anthropological education for missionaries in America more than anyone else in the interwar period. Donohugh's story provides a window into understanding how anthropology was first used in mission education in America.